“Developing Creative Competencies through the Integration of Visual Arts in School and Higher Education” - Aslonova Shaxnoza Islom qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article discusses the integration of visual arts in school and higher education and its role in developing students’ creative competencies. Research indicates that skills acquired at the school level are further deepened in higher education, allowing students to engage in complex graphic projects, interactive design tasks, and independent creative work. The integration of visual arts fosters cognitive, aesthetic, and professional development in students, preparing them for future artistic and creative careers.